Comparison of Fiber Characteristics of Empthy Fruit Bunches (EFB) after Steaming and Boiling Treatment in Pulp Synthesis - Lestari Hetalesi Saputri; Muhammad Hafiz; Muhammad Fadli (PT FORMOSA CENDEKIA GLOBAL, 2023)
Empthy Fruit Bunches (EFB) is biomass from Palm Oil Mills with high cellulose content. Cellulose can be used for the manufacture of coatings, clothing fibers, bioplastics, papers and membranes. Obtaining pure cellulose for these products generally is begun with the stages of removing the following impurities, through steaming or boiling. This study aims to compare the characteristics of the EFB fiber from the two processes. Comparisons were made by steaming and boiling EFB fiber at 80℃ for 30, 60, 90 and 120 minutes. The fibers was tested for water absorption, density and tensile strength. The test results showed that the boiling process produced brighter colored fibers, tensile strength and water absorption were also better with values of 107.40 kgf/cm2 and 62.46%. Meanwhile, for the density value is is the same for each variation.